2020
DOI: 10.1503/jpn.190027
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, treatment and Tetris: video gaming increases hippocampal volume in male patients with combat-related posttraumatic stress disorder

Abstract: Background: Tetris has been proposed as a preventive intervention to reduce intrusive memories of a traumatic event. However, no neuro imaging study has assessed Tetris in patients with existing posttraumatic stress disorder (PTSD) or explored how playing Tetris may affect brain structure. Methods: We recruited patients with combat-related PTSD before psychotherapy and randomly assigned them to an experimental Tetris and therapy group (n = 20) or to a therapy-only control group (n = 20). In the control group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 60 publications
2
32
0
1
Order By: Relevance
“…The entorhinal cortex receives converging input from many areas of the cortex and projects this information to the hippocampus (Li et al., 2017). Therefore, our finding in the entorhinal cortex could be linked to previous findings of treatment‐related increases in hippocampal volume among adults with PTSD (Butler et al., 2020).…”
Section: Discussionsupporting
confidence: 82%
“…The entorhinal cortex receives converging input from many areas of the cortex and projects this information to the hippocampus (Li et al., 2017). Therefore, our finding in the entorhinal cortex could be linked to previous findings of treatment‐related increases in hippocampal volume among adults with PTSD (Butler et al., 2020).…”
Section: Discussionsupporting
confidence: 82%
“…Fifteen studies involved healthy participants, in most cases recruited from university staff and students, whereas three studies recruited participants among full-time workers [ 82 ], soldiers [ 86 ], and older adults in federal programs for assistance [ 117 ]. The other studies included soldiers who had posttraumatic stress disorder [ 113 ]; older adults who lived in a nursing home [ 112 ] and with Parkinson disease [ 109 ]; adults with at least minimal symptoms of depression [ 114 ], clinical depression, and comorbid anxiety [ 102 ], systemic lupus erythematosus [ 122 ], obesity [ 108 ], physical disabilities [ 116 ], and hematologic malignancies [ 105 ]; women after emergency cesarean section [ 115 ]; children with molar incisor hypomineralization–affected teeth [ 103 ], chronic wounds on the lower limbs that require active dressing changes [ 110 ], and who sustained second- and third-degree burns to the shoulders, neck, chest, bilateral forearms, and left thigh [ 123 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, 7 studies used Nintendo Wii Fit, 5 studies used Microsoft Xbox 360 with Xbox Kinect, 1 study used tXbox One [107], and 1 study used Sony PlayStation 3 [108]. Nine studies used a PC, three studies used a virtual reality viewer [103,110,119], one study used a smartphone [82], and two studies used a portable console (ie, Nintendo DS and Nintendo DS XL) [113,115].…”
Section: Platformmentioning
confidence: 99%
“…In these studies, Tetris gameplay was also associated with activations in the occipital and parietal lobes (Haier et al, 2009;Price et al, 2013) as well as the premotor areas (Haier et al, 2009). Notably, we did find a local maxima (Supplementary Table S1) and many activated voxels within the hippocampus (Supplementary Table S2), an area in which volume has been observed to increase with daily Tetris gameplay practice (3 months; Butler et al, 2020). In the current study, the global peak during Tetris gameplay, controlling for motor activity, was in the middle temporal gyrus (Table 1).…”
Section: Discussionmentioning
confidence: 63%
“…Tetris gameplay has previously been used in neuroimaging studies to investigate brain activity in emotion regulatory neural circuits (amygdala and occipital cortex; Price et al, 2013), to examine the impact of repeated practice of a visuospatial/ motor task on overall brain activity (Haier et al, 1992;Rietschel et al, 2012), and to assess the plasticity of cortical grey matter (Haier et al, 2009). Also, a neuroimaging study on posttraumatic stress disorder (PTSD) showed that daily Tetris gameplay (3 months), in conjunction with psychological treatment, increased hippocampal volume, which was associated with PTSD symptom reduction (Butler et al, 2020). However, there is a need for further neuroimaging studies pinpointing the visuospatial aspects of Tetris gameplay.…”
Section: Introductionmentioning
confidence: 99%